Artemisia vulgaris Induces Tumor-Selective Ferroptosis and Necroptosis via Lysosomal Ca2+ Signaling - Zamarioli, Lucas dos Santos; Santos, Michele Rosana Maia; Erustes, Adolfo Garcia; Meccatti, Vanessa Marques [UNESP]; Pereira, Thaís Cristine [UNESP]; Smaili, Soraya S.; Marcucci, Maria Cristina [UNESP]; Oliveira, Carlos Rocha; Pereira, Gustavo J. S.; Bincoletto, Claudia (Springer Nature, 2024)
Objective: To evaluate the chemical composition and effects of Artemisia vulgaris (AV) hydroalcoholic extract (HEAV) on breast cancer cells (MCF-7 and SKBR-3), chronic myeloid leukemia (K562) and NIH/3T3 fibroblasts. Methods: Phytochemical analysis of HEAV was done by high-performance liquid chromatography-mass (HPLC) spectrometry. Viability and cell death studies were performed using trypan blue and Annexin/FITC-7AAD, respectively. Ferrostatin-1 (Fer-1) and necrostatin-1 (Nec-1) were used to assess the mode of HEAV-induced cell death and acetoxymethylester (BAPTA-AM) was used to verify the involvement of cytosolic calcium in this event. Cytosolic calcium measurements were made using Fura-2-AM. Results: HEAV decreased the viability of MCF-7, SKBR-3 and K562 cells (P<0.05). The viability of HEAV-treated K562 cells was reduced compared to HEAV-exposed fibroblasts (P<0.05). Treatment of K562 cells with HEAV induced cell death primarily by late apoptosis and necrosis in assays using annexin V-FITC/7-AAD (P<0.05). The use of Nec-1 and Fer-1 increased the viability of K562 cells treated with HEAV relative to cells exposed to HEAV alone (P<0.01). HEAV-induced Ca2+ release mainly from lysosomes in K562 cells (P<0.01). Furthermore, BAPTA-AM, an intracellular Ca2+ chelator, decreased the number of non-viable cells treated with HEAV (P<0.05). Conclusions: HEAV is cytotoxic and activates several modalities of cell death, which are partially dependent on lysosomal release of Ca2+. These effects may be related to artemisinin and caffeoylquinic acids, the main compounds identified in HEAV.
Keywords: Artemisia vulgaris; Ca2+ signaling; ferroptosis; late apoptosis; necroptosis